2019
DOI: 10.29309/tpmj/2019.26.06.3614
|View full text |Cite
|
Sign up to set email alerts
|

Detection of methicillin resistant staphylococcus aureus using mec a, ribotyping and antibiogram profile of Pakistani clinical isolates

Abstract: Background: The objective of this study was to determine the incidence of MRSA with their antibiotic susceptibility pattern and molecular characterization of these strains. Study Design: Cross sectional study. Setting: Microbiology section of Citilab and Research Centre, Lahore. Period: March 2014 to June 2016. Materials and Methods: Bacterial isolates were retrieved from different specimens of pus/wound, blood and other body fluids. These were characterized using conventional (catalase, DNase, coagulase etc),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…These results are similar to our results in which high susceptibility was found against vancomycin (100%) and linezolid (98%) followed by clindamycin (81%) and rifampicin (77.3%). 4 While another study conducted in Saudi Arabia showed slight different results reporting 60% resistance against penicillin while high susceptibility for clindamycin (85%). 22…”
Section: Discussionmentioning
confidence: 96%
“…These results are similar to our results in which high susceptibility was found against vancomycin (100%) and linezolid (98%) followed by clindamycin (81%) and rifampicin (77.3%). 4 While another study conducted in Saudi Arabia showed slight different results reporting 60% resistance against penicillin while high susceptibility for clindamycin (85%). 22…”
Section: Discussionmentioning
confidence: 96%
“…This combined pattern of resistance with MRSA signals towards presence of gyr A, B mutations and erm genes along with mecA gene. Maximum sensitivity has been shown to glycopeptides and linezolid by some researchers [13,15,18].…”
Section: Discussionmentioning
confidence: 99%